Trade flows and the international business cycle - Daniel Gross (Goethe University Frankfurt, Center for Financial Studies (CFS), 2001)
We investigate into the role of the trade channel as important determinant of a country's current account position and the degree of business cycle synchronization with the rest of the world by comparing the predictions of two types of DGE models. It is shown that the behavior of a country's external balance and the international transmission of shocks depends amongst other things on two factors: i) the magnitude of trade interdependence, ii) the degree of substitutability between importable and domestically-produced goods. Using time series data on bilateral trade flows, we estimate the magnitude of trade interdependence and the elasticity of substitution between importable and domestic goods for the G7 countries. Given these estimates, idiosyncratic supply shocks potentially induce changes in the current account and foreign output that vary in direction and magnitude across G7 countries. The relationship between the magnitude of foreign trade and the import substitutability with various correlation measures is examined empirically in a cross-sectional dimension.
urn:nbn:de:hebis:30-9890
Keywords: E32; F41; 330; Intratemporal Elasticity of Substitution; Bilateral Trade Flows; Current Account; DGE Models